Electroexcitation of the Δ+(1232) at low momentum transfer - A. Blomberg (2018)
© 2016 The Authors We report on new measurements at the resonance at the low momentum transfer region, where the mesonic cloud dynamics is predicted to be dominant and rapidly changing, offering a test bed for chiral effective field theory calculations. The new data explore the dependence of the resonant quadrupole amplitudes and for the first time indicate that the Electric and the Coulomb quadrupole amplitudes converge as. The measurements of the Coulomb quadrupole amplitude have been extended to the lowest momentum transfer ever reached, and suggest that more than half of its magnitude is attributed to the mesonic cloud in this region. The new data disagree with predictions of constituent quark models and are in reasonable agreement with dynamical calculations that include pion cloud effects, chiral effective field theory and lattice calculations. The measurements indicate that improvement is required to the theoretical calculations and provide valuable input that will allow their refinements.